2015
DOI: 10.1007/s12020-015-0795-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to electromagnetic radiation from mobile phones and Wi-Fi devices decreases plasma prolactin, progesterone, and estrogen levels but increases uterine oxidative stress in pregnant rats and their offspring

Abstract: TRPV1 cation channels are the possible molecular pathways responsible for changes in the hormone, oxidative stress, and body temperature levels in the uterus of maternal rats following a year-long exposure to electromagnetic radiation exposure from mobile phones and Wi-Fi devices. It is likely that TRPV1-mediated Ca(2+) entry in the uterus of pregnant rats involves accumulation of oxidative stress and opening of mitochondrial membrane pores that consequently leads to mitochondrial dysfunction, substantial swel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…Moreover, Shi et al, [25] and Al-Akhras [26] reported that the levels of FSH, LH, estrogen and progesterone were significantly decreased after exposure of the gravid and non-gravid rats to ELF of 50 Hz EMR. Furthermore these findings are confirmed by the results obtained from Yuksel et al, [22] and Shahin et al [23] who detected that exposure to 900 , 1800 and 2450 MHz EMR causes decrease in FSH, LH, estrogen, progesterone and prolactin levels in maternal and growing rats. In contradiction to the above results, it was reported that the plasma progesterone and estrogen levels in rats were not changed by ELF (50Hz) induced EMR exposure [27].…”
Section: (Figure3)supporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, Shi et al, [25] and Al-Akhras [26] reported that the levels of FSH, LH, estrogen and progesterone were significantly decreased after exposure of the gravid and non-gravid rats to ELF of 50 Hz EMR. Furthermore these findings are confirmed by the results obtained from Yuksel et al, [22] and Shahin et al [23] who detected that exposure to 900 , 1800 and 2450 MHz EMR causes decrease in FSH, LH, estrogen, progesterone and prolactin levels in maternal and growing rats. In contradiction to the above results, it was reported that the plasma progesterone and estrogen levels in rats were not changed by ELF (50Hz) induced EMR exposure [27].…”
Section: (Figure3)supporting
confidence: 75%
“…Moreover in concordance to the current data, Aksen et al, [21] stated that prolonged exposure to 50 Hz induced increasing in MDA levels in rat uterus and ovaries. Also Yuksel et al, [22] and Shahin et al [23] who demonstrated that mobile phones emitting 900 and 1800 MHz and Wi-Fi emitting 2450 MHz EMR induced modification in the concentrations of local uterine oxidative stress markers of growing and maternal rats associated with drop in the plasma concentration of vitamin C, E and A. On the other hand, in contrast to the present results Kismali et al, [13] detected nonsignificant difference of oxidative stress markers in the blood of pregnant rabbits after EMR exposure.…”
Section: (Figure3)mentioning
confidence: 94%
“…Mobile phone use during pregnancy has been reported to be associated with an increased risk for behavioral problems in children 3 . Previous studies have suggested that low frequency EMF may cause various adverse effects in the fetus, including increased oxidative stress and oxidative uterine injury 4,5 , non-reversible changes occurring in the critical stages of egg development and potential fetal death [6][7][8][9] . Low frequency EMF also affects the embryo's heart rate, newborn growth, and hippocampal integrity in the fetus 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The radiation frequency emitted from mobile phones and their base station antennae ranges from 900-1800 MHz for the Global System for Mobile Communications [1], which belongs to hyperfrequency electromagnetic fields (EMFs) [2]. The extensive use of mobile phones has been accompanied by possible adverse effects on human health, especially the male reproductive system.…”
Section: Introductionmentioning
confidence: 99%